Menggagas Penerapan Judicial Restraint Di Mahkamah Konstitusi - Wicaksana Dramanda (Jurnal Konstitusi, 2016)
Many controversial decision made by Constitutional Court resulted in the emergence of the idea to limit the judicial power. One of the ideas that surfaced to limit the judicial power without disturbing the idea of judicial independence is judicial restraint. The idea of judicial restraint puts limitation on certain forms. The forms of limitation under judicial restraint could be limitation based on constitutional norms, limitation based on policies for restraint (self-restraint), and the limitation imposed by certain doctrines. Judicial restraint requires the judicial power to refrain from tendencies to act like a mini parliament   that can lead to the juristocracy. Judicial restraint also requires judicial power not interfere the other branches of power.